Puasa Ramadlan dalam Kajian Kitab Nihayatuz Zain (Analisis dari Persepektif Fiqih, Tasawuf dan Kesehatan) - Aminah , Siti; Musthofa, R. Zainul (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
The Book of Nihayatuz Zain is one of the books by Indonesian scholars, namely scholars who have recognized their knowledge and wisdom as well as their expertise in the field of science, especially religious sciences. His expertise and expertise in science are not only recognized and recognized in the national or domestic scope, but also have reached overseas or international scope. He is Sheikh Imam Nawawi al Bantani. The Book of Nihayatuz Zain is a book of Fiqh based on the As-Syafi'i school, which is quite well known in Indonesia. This book is a syarah from the book "Qurratul Ain", the work of al Malibari. The Book of Nihayatuz Zain was written by Sheikh Nawawi al Bantani with short, concise Lafadz and using easy-to-understand language. And for the arrangement in the book of Nihayatuz Zain, it follows the arrangement of the book in its syarah, namely the book "Qurratul Ain", starting with the prayer chapter and ending with the slave liberation chapter. In this article, the author will raise one of the discussions from the book of Nihayatuz Zain, namely the chapter on Ramadan fasting because Ramadan fasting is one of the pillars of Islam. In discussing Ramadan fasting this time, the author does not only examine it from the fiqh perspective, but also from the other side, namely from the perspective of Sufism and Health. So that later this paper is expected to be a multidisciplinary study that can be viewed from various perspectives and can be useful for Muslims as a whole, and Muslims can carry out fasting perfectly according to the guidance of Allah SWT and Rasulullah SAW.